Empirical models of cosmic ray propagation in the Galaxy - Ptuskin, V. S. (Astrophysics and space science, 1974)
The homogeneous and flat diffusion models of the propagation of cosmic rays through the Galaxy are considered. It is shown that, with the usual choice of galactic parameters, in particular, those pertaining to its gas distribution, and subject to the restriction of not too heavy nuclei (nuclei no heavier than iron), both models are equivalent from the point of view of the description of the element composition of cosmic rays. This conclusion is justifiable both for galactic and metagalactic theories of the occurrence of cosmic rays. A connection is established between the effective path length of the matter which nuclei encounter in the Galaxy and the parameters of the diffusion model with an inhomogeneous distribution of an interstellar gas. Initial results allow the interpretation of a relationship of cosmic ray element composition to their energies. Restrictions which must be placed on such a relationship are shown from the different data on cosmic rays at the earth.